2018
DOI: 10.3390/rs10060920
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Remote Sensing Image Classification Method Based on Convolutional Neural Network and Restricted Conditional Random Field

Abstract: Abstract:Convolutional neural networks (CNNs) can adapt to more complex data, extract deeper characteristics from images, and achieve higher classification accuracy in remote sensing image scene classification and object detection compared to traditional shallow-model methods. However, directly applying common-structure CNNs to pixel-based remote sensing image classification will lead to boundary or outline distortions of the land cover and consumes enormous computation time in the image classification stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…This paper presents a workflow that has identified rock outcrops with an overall 0.95 F1 Macro for eight test sites, which is an improvement over the mere 0.53-0.75 overall accuracy of the existing datasets (e.g., Figure 1). This model, which specifically adds rock identification, performed as well if not better than those of previous similar CNN studies that had 0.82-0.95 overall accuracy rates [20,22,47]. Therefore, the method presented here offers a large improvement over what is currently available for barren or rock classification, even if it does not refine the class labeled other.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This paper presents a workflow that has identified rock outcrops with an overall 0.95 F1 Macro for eight test sites, which is an improvement over the mere 0.53-0.75 overall accuracy of the existing datasets (e.g., Figure 1). This model, which specifically adds rock identification, performed as well if not better than those of previous similar CNN studies that had 0.82-0.95 overall accuracy rates [20,22,47]. Therefore, the method presented here offers a large improvement over what is currently available for barren or rock classification, even if it does not refine the class labeled other.…”
Section: Discussionmentioning
confidence: 56%
“…Maltezos and Doulamis [46] implemented CNN for extracting buildings orthoimages using the height information as an additional feature. Pan and Zhao [47] proposed a classification method based on CNN and the restricted conditional random field algorithm (CNN-RCRF) to classify land cover into six classes (impervious surfaces, buildings, low vegetation, trees, cars, and clutter/background) using high-resolution remote sensing images. This method was used to avoid boundary distortions of the land cover and reduce computation time in classifying images.…”
Section: Potential Classification Modelsmentioning
confidence: 99%
“…This process leads to some ground objects being excessively enlarged or reduced. Furthermore, if the different parts of ground objects that are shadowed or not shadowed are processed in the same manner, the CRF result will contain more errors [31]. In our previous work, we proposed a method called the restricted conditional random field (RCRF) that can handle the above situation [31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if the different parts of ground objects that are shadowed or not shadowed are processed in the same manner, the CRF result will contain more errors [31]. In our previous work, we proposed a method called the restricted conditional random field (RCRF) that can handle the above situation [31]. Unfortunately, the RCRF requires the introduction of samples to control its iteration termination and produce an output integrated image.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, domain-specific knowledge (e.g., spatial dependency [32] and multiscaling) related to remote sensing and the geosciences has not, or only partially, been considered and embedded in these models. Although fully connected CRFs [33] may be used to encode such domain knowledge, only limited related studies [34,35] have been reported in the field of remote sensing.…”
Section: Introductionmentioning
confidence: 99%